EXAMINING THE EFFECT OF CLIMATE CHANGE ON THE SUSCEPTIBILITY OF ROAD PAVEMENTS IN SOUTH-SOUTH NIGERIA USING THE DELPHI METHOD - E. Isemede, Eric (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2023)
Asphalt pavements constitute a high portion of Nigeria's roadways, which have high traffic volumes. The potential deterioration in the long-term performance of these pavements due to climate change has not been given much research attention. To this extent, the present study evaluated the pavement susceptibility of Federal roads in Edo state of South-South Nigeria. The study employed the Delphi technique to examine expert opinions. The standard deviation of the answers to two rounds of questionnaires was used to evaluate the consensus reached by the 10-person Delphi panel. The result showed that one of the four federal roads analyzed in the study was classified as having a high susceptibility, two were classified as having a medium susceptibility, and the remaining road was classified as having a low susceptibility. This research demonstrates that the Delphi technique, which incorporates both objective and subjective assessments, can comprehensively evaluate road pavements' vulnerability to climate change. Therefore, the government should employ adaptive maintenance plans for the roads' varying degrees of susceptibility.